2013
DOI: 10.1111/obr.12013
|View full text |Cite|
|
Sign up to set email alerts
|

Post‐operative behavioural management in bariatric surgery: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Recent research has provided evidence that bariatric surgery maximizes long-term weight loss in patients with severe obesity. However, a substantial number of patients experience poor weight loss outcome and weight regain over time. Post-operative behavioural management may facilitate long-term weight control in bariatric surgery population. The objective of this systematic review and meta-analysis was to determine the effects of post-operative behavioural management on weight loss following bariatric surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 62 publications
6
102
0
4
Order By: Relevance
“…It has been argued that patient's follow-up by interdisciplinary specialized group is important after surgery to monitor weight changes, medical comorbidities and long-term surgical adverse events, such as multiple nutrient deficits. 2,13,14 Nevertheless, most major RYGBP series have shown a 60-50% postoperative follow-up rate at 1 year, which drops off dramatically with time. 15 These estimates are similar to the overall adherence prevalence of 51% (95%CI: 44.5-57.5%) during the 18-month follow-up period of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that patient's follow-up by interdisciplinary specialized group is important after surgery to monitor weight changes, medical comorbidities and long-term surgical adverse events, such as multiple nutrient deficits. 2,13,14 Nevertheless, most major RYGBP series have shown a 60-50% postoperative follow-up rate at 1 year, which drops off dramatically with time. 15 These estimates are similar to the overall adherence prevalence of 51% (95%CI: 44.5-57.5%) during the 18-month follow-up period of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart and Avenell included eight pre-surgery and post-surgery behavioral intervention studies in their meta-analysis and concluded that patients receiving behavioral interventions resulted in greater weight change when added to bariatric surgery in comparison to surgery alone [3]. This review also suggested that post-operative interventions had greater evidence than pre-surgery interventions for improving weight loss outcomes [3], which is further reinforced by a meta-analysis of five randomized controlled trials demonstrating greater weight loss with post-operative behavioral lifestyle interventions compared to surgery alone [2]. However, these reviews cautioned interpretation of their results and called for greater research in this area.…”
Section: Introductionmentioning
confidence: 97%
“…Systematic reviews and meta-analyses of pre-and post-bariatric surgery individual and group psychotherapeutic interventions, have shown greater weight loss in comparison to control groups, with a moderate effect size (pooled effect size correlation = 0.18) for weight loss after bariatric surgery [1,2]. Stewart and Avenell included eight pre-surgery and post-surgery behavioral intervention studies in their meta-analysis and concluded that patients receiving behavioral interventions resulted in greater weight change when added to bariatric surgery in comparison to surgery alone [3].…”
Section: Introductionmentioning
confidence: 99%
“…Among other factors, dysfunctional eating behaviors such as emotional eating, binge eating and loss of control over eating, have been indicated as negative psychological factors for treatment outcome [3,4]. As such, behavioral life style interventions seem important to achieve optimal weight loss results [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this protocol patients receive 10 sessions of CBT focused on nutritional and activity management (session 1-4), cognitive restructuring and self-control (session [5][6][7][8] and relapse prevention strategies and preparation for the period after surgery (session 9-10). See Table 1 for an overview of the interventions in the 10 sessions.…”
Section: Introductionmentioning
confidence: 99%